Development of Information Technology Application in Education in Indonesia - Aneng Aisyah; Agus Setiawan; Rama Wijaya Abdul Rozak (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract Information technology plays an important role in modern education by improving access and quality of learning. This study aims to examine the development of information technology application in education in Indonesia through qualitative research methods and analysis of related literature. The results of the study indicate that the development of information technology in education in Indonesia can be divided into three eras: the Pre-Digital Era with traditional learning methods and limited access to information; the Early Digital Era with the introduction of computers in schools and support from government programs for information technology integration; and the Modern Information Technology Era with increased internet access, e-learning, distance learning, and technology-based curriculum innovation. The positive impacts of information technology application include increased accessibility, quality of learning, and development of digital skills. However, this application also has negative impacts such as inequality in access to technology, dependence on technology, and challenges in management and implementation. In conclusion, the application of information technology in education in Indonesia has grown significantly and has had a major impact on the education system. However, there are still challenges that need to be overcome to ensure that the benefits of information technology can be felt by all students and educators. Keywords: Information technology, Positive impacts, Qualitative research